Heat: A Highly Efficient Skin Enhancer for Transdermal Drug Delivery - Szunerits, Sabine; Boukherroub, Rabah (Frontiers in Bioengineering and Biotechnology, 2018)
Advances in materials science and bionanotechnology have allowed the refinements of current drug delivery systems, expected to facilitate the development of personalized medicine. Whereas dermatological topical pharmaceutical formulations such as foams, creams, lotions, gels etc. have been proposed for decades, these systems target mainly skin based diseases. To treat systemic medical conditions as well as localized problems such as joint or muscle concerns, transdermal delivery systems (TDDS), which use the skin as the main route of drug delivery, are very appealing. Over the years, these systems have shown to offer important advantages over oral as well as intravenous drug delivery routes. Besides being non-invasive and painless, TDDS are able to deliver drugs with a short-half-life time more easily, and are well adapted to eliminate frequent administrations to maintain constant drug delivery. The possibility of self-administration of a pre-determined drug dose at defined time intervals makes it also the most convenient personalized point-of care approach. The transdermal market still remains limited to a narrow range of drugs. While small and lipophilic drugs have been successfully delivered using TDDS, this approach fails to deliver therapeutic macromolecules due to size-limited transport across the stratum corneum, the outermost layer of the epidermis. The low permeability of the stratum corneum to water-soluble drugs as well as macromolecules poses important challenges to transdermal administration. To widen the scope of drugs for transdermal delivery, new procedures to enhance skin permeation to hydrophilic drugs and macromolecules are under development. Next to iontophoresis and microneedle based concepts, thermal based approaches have shown great promise to enhance transdermal drug delivery of different therapeutics. In this inaugural article for the section “Frontiers in Bioengineering and Biotechnology”, the advances in this field and the handful of examples of thermal technologies for local and systemic transdermal drug delivery will be discussed and put into perspective.